The Multi-Dimensional Nature of Poverty in Djibouti - Mendiratta, Vibhuti; Duplantier, Anne (World Bank, Washington, DC, 2020)
This note illustrates the multidimensional nature of poverty in Djibouti. The authors use the multidimensional poverty index (MPI), which captures several welfare dimensions - monetary poverty, education, and access to basic infrastructure - to compare the extent to which different populations in Djibouti are deprived: rural versus urban, households where the head is educated versus not, households where the head is employed versus not, among other characteristics. Overall, about 28 percent of the population is multidimensionally poor and wide disparities exist across geographic locations. Moreover, people living in a household headed by a person who is educated and employed in the formal private sector are least likely to be multidimensionally poor.